Programa Nacional de Avaliação dos Serviços de Saúde PNASS 2015-2016: um olhar sobre os hospitais em Minas Gerais. - Giselle Bianca Tófoli (2021)
The study aims to describe the hospitals in Minas Gerais that participated in the PNASS 2015-2016 and evaluate their performance. It is a descriptive cross-sectional study, of a quantitative nature, involving the use of secondary data, of public access, which sought to verify the performance of the Minas Gerais hospitals that participated in the program from the data of the first PNASS 2015-2016 assessment instrument - Check Items Roadmap. The process evaluation questionnaire answered by hospitals had 180 items and 30 criteria, grouped into five blocks. 208 Minas Gerais hospitals participated, of which the majority are medium sized, making a total of 73.08% of the institutions evaluated in this study. The average score per block was: 1) Organizational Management (66); 2) Technical and logistical support for the production of care (77); 3) Management of Health Care and Care (68) and 4) Specific Services / Units (76) and 5) Oncology Assistance (84). The hospitals that achieved the best performance of the general indicator are located in the health macro-regions of the Northern Triangle (83.46), Jequitinhonha (82.83), Southeast (76.84) and Center (75.59). Special and large hospitals performed better. Regarding the administrative sphere, of the total hospitals evaluated in Minas Gerais, 78.37% are private / contracted and only 21.63% public (federal, state and municipal), however the best average performance was obtained by the Federal public sphere, followed by State. Hospitals under municipal management also achieved the best results. It was observed that about 60% of the evaluated hospitals had excellent and good performance, showing that they maintain adequate processes for achieving quality. The findings point to the advancement of municipalization in the state, however, important inequalities were identified between the health macro-regions of Minas Gerais in relation to the number and complexity of hospitals, indicating the need to deepen the regionalization process, with shared management and solidary, efficient regulation in the agreement of contracts, which considers the inter-federative articulation for the implementation of the health care networks and the institutionalization of the culture of evaluation of the hospitals that make up the SUS, so that the citizens have access to these services according to their needs and as close as possible to where they live.